Optimizing day-ahead power scheduling: A novel MIQCP approach for enhanced SCUC with renewable integration - Sina Samadi Gharehveran; Kimia Shirini; Selma Cheshmeh Khavar; Arya Abdollahi (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
This paper introduces an innovative methodology aimed at enhancing day-ahead power system scheduling by incorporating adaptable technologies within the framework of security-constrained unit commitment. The methodology is tailored for power systems characterized by significant integration of photovoltaic energy, with the goal of reducing operational expenses linked to energy storage systems, demand response initiatives, solar power curtailment, and load shedding. The scheduling issue is structured as a mixed-integer quadratically-constrained programming model, which guarantees globally optimal solutions for intricate, real-world applications. The developed model has been implemented using the GAMS and tested through extensive case studies on the IEEE 24-bus system. The findings reveal that the strategic coordination of flexible resources leads to a 5.6 % reduction in scheduling costs compared to traditional methods. This result highlights the model's effectiveness in improving operational efficiency and cost savings for power systems with high renewable energy penetration, establishing it as an essential tool for sustainable management of power systems.